Impaired cognitive self-awareness mediates the association between alexithymia and excitation/inhibition balance in the pgACC. Issue 10 (22nd July 2020) - Kühnel, A.; Widmann, A.; Colic, L.; Herrmann, L.; Demenescu, L. R.; Leutritz, A. L.; Li, M.; Grimm, S.; Nolte, T.; Fonagy, P.; Walter, M.
Abstract: Background: Previous research showed that automatic emotion regulation is associated with activation of subcortical areas and subsequent feedforward processes to cortical areas. In contrast, cognitive awareness of emotions is mediated by negative feedback from cortical to subcortical areas. Pregenual anterior cingulate cortex (pgACC) is essential in the modulation of both affect and alexithymia. We considered the interplay between these two mechanisms in the pgACC and their relationship with alexithymia. Method: In 68 healthy participants (30 women, age = 26.15 ± 4.22) we tested associations of emotion processing and alexithymia with excitation/inhibition (E/I) balance represented as glutamate (Glu)/GABA in the pgACC measured via magnetic resonance spectroscopy in 7 T. Results: Alexithymia was positively correlated with the Glu/GABA ratio ( N = 41, p = 0.0393). Further, cognitive self-awareness showed an association with Glu/GABA ( N = 52, p = 0.003), which was driven by a correlation with GABA. In contrast, emotion regulation was only correlated with glutamate levels in the pgACC ( N = 49, p = 0.008). Conclusion: Our results corroborate the importance of the pgACC as a mediating region of alexithymia, reflected in an altered E/I balance. Furthermore, we could specify that this altered balance is linked to a GABA-related modulation of cognitive self-awareness of emotions.